EFFECTS OF SOCIETAL STEREOTYPE AGAINST CHILDREN WITH SPECIAL NEEDS - Wardiansyah, Jumi Adela; Lessy, Zulkipli; Dalvi, Haresh B (UIN Sunan Kalijaga Yogyakarta, 2021)
This research aims to advocate society not to stereotype against children with disabilities, such as those with autism and blindness, and how parents and teachers take significant roles in educating and undergoing a therapy so that the children grow and develop properly. Parents and teachers take these actions, so society receive these children with special needs, and thus are able to participate in society. The research was conducted at the village of Lingkok Busu, Pidie Regency of Aceh by using the qualitative study, in that it typically employs a study case approach focusing on a specific unique locus. The researchers gathered data by means of observations and interviews. The participants are two children each with autism and blindness, three teachers, at Special Primary School Rapana, who accompany the students in developing their abilities. Of these two teachers, one serves as a parent. Results show that there should be a mutual teacher-parent cooperation to address the societal stereotypes against the children, who are considered unfortunate in society. Therefore, it is necessary to have a religious and cross-cultural counseling so that we all live together peacefully with the slogan of Bhinneka Tunggal Ika (unity in diversity) regardless of the country’s myriad cultures, ethnicities, languages, religions, or political affiliations, and so Indonesians have a true sense of unity. The researchers conclude that the children with autism and blindness should participate in society, and the roles of parents and teachers are to augment their potential; thus, they will grow and function well in society.